Artificial intelligence technologies and the evolution of Web 3.0 - Issa, Tomayess; Isaias, Pedro (Hershey, PA : Information Science Reference, 2015)
'This book brings together emergent research and best practices surrounding the effective usage of Web 3.0 technologies in a variety of environments'--
Includes bibliographical references and index.
Keywords: Semantic Web; Artificial intelligence; Web databases; Educational Web sites